2017
DOI: 10.1037/pas0000427
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Brief Symptom Inventory-18 (BSI-18) for identifying depression and anxiety in young adult cancer survivors: Comparison with a Structured Clinical Diagnostic Interview.

Abstract: The Brief Symptom Inventory-18 (BSI-18) is widely used to assess psychological symptoms in cancer survivors, but the validity of conventional BSI-18 cut-off scores in this population has been questioned. This study assessed the accuracy of the BSI-18 for identifying significant anxiety and depression in young adult cancer survivors (YACS), by comparing it to a “gold standard” diagnostic interview measure. Two hundred and fifty young adult cancer survivors (YACS), age 18–40 completed the BSI-18 and the Structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 72 publications
4
43
1
2
Order By: Relevance
“…A highly accurate depression screen in YACS would be very useful for oncologists and other providers, who could rely on it in a similar manner to determine which YACS require further evaluation for depression. Unfortunately, consistent with the results of studies of several other symptom checklist screening measures, the current study results indicated that the PROMIS‐D‐SF is not sufficiently sensitive and specific to be used as a stand‐alone screening tool for depression in YACS.…”
Section: Discussionsupporting
confidence: 62%
“…A highly accurate depression screen in YACS would be very useful for oncologists and other providers, who could rely on it in a similar manner to determine which YACS require further evaluation for depression. Unfortunately, consistent with the results of studies of several other symptom checklist screening measures, the current study results indicated that the PROMIS‐D‐SF is not sufficiently sensitive and specific to be used as a stand‐alone screening tool for depression in YACS.…”
Section: Discussionsupporting
confidence: 62%
“…71,72 Taken together, our current results confirm the usefulness of the BSI in its original 53-item form for screening and case finding in patients with cancer who have a definite psychiatric diagnosis, as assessed by a standardized clinical interview instead of other nondiagnostic psychometric tools used in other studies. Regarding the BSI-18, we confirmed the caveats for the use of case-rule cutoff scores recently raised by Recklitis et al 39 in young adult survivors of cancer, indicating that, compared with using psychiatric interviews to make psychiatric diagnoses according to the DSM, general concordance between the BSI-18 GSI scale and psychiatric diagnosis was good; however, the 2 most widely used BSI-18 case rules failed to identify the majority of survivors who had a DSM psychiatric diagnosis. In our study, we indeed confirmed that the Recklitis et al GSI T-score cutoff of 50 maximized sensitivity and specificity for case detection; however, we also identified another cutoff score (48) that supported the clinical value of the BSI-18.…”
Section: Discussionsupporting
confidence: 86%
“…A strong limitation of current research is that very few data are available regarding the case‐finding properties of the BSI‐18 compared with a formal psychiatric assessment, which indeed is the reference gold standard for diagnosis, rather than the other psychometric tools used in most studies to examine accuracy in detecting caseness. With respect to this, a recent study of 250 young adult cancer survivors indicated that the BSI‐18 had good overall concordance with the SCID psychiatric interview for making diagnoses according to the DSM, but the recommended cutoff scores failed to identify the majority of patients with psychiatric diagnosis …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, GSI T-scores ≥ 63 was considered as the high-risk group for psychological symptoms and GSI T-scores < 63 as was considered as the low-risk group for psychological symptoms with for further psychological evaluation. The GSI T-score threshold has been proven valid and reliable marker for identifying severe psychological condition that requires assessment and possible intervention, and it has been used extensively in psychological researches in recent years (Arneiro et al, 2018;Black et al, 1998;Fauerbach et al, 2007;Monteiro et al, 2017;Otte et al, 2017;Recklitis et al, 2017).…”
Section: Methodsmentioning
confidence: 99%